PENGUATAN PENDIDIKAN KARAKTER BERBASIS KEARIFAN LOKAL TRI HITA KARANA PARA SISWA HINDU - I Putu Gede Parmajaya (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
With the development of advances in science and technology (Science and Technology) brings positive and negative influences on human mindset, especially on the world of education. Strengthening character education (PPK) aims to: (1) build and equip students as the golden generation of Indonesia in 2045 to face the dynamics of change in the future, (2) develop a national education platform that places character education as the main soul by paying attention to the diversity of Indonesian culture , and (3) revitalizing and strengthening the potential and competence of the education ecosystem. In terms of providing reinforcement for character education, a strong foundation must be found to build aspects of character strengthening such as: (1) religious, (2) Nationalist, (3) Independent, (4) integrity and mutual cooperation. In Hindu teaching, one of the concepts of the teaching that has been recognized by the world in achieving the five aspects of KDP above is the teaching or tradition of tri hita karana, as a form of local wisdom guided by Hindus in social, religious, national and state life. Key Word: Strengthening, Character Education, and tri hita karana